Tracheoesophageal Fistula due to a Damaged Tracheal Stent - Masahiro Kimura; Yoshiyuki Kuwabara; Hideyuki Ishiguro; Tatsuya Tanaka; Hiromitsu Takeyama (Case Reports in Surgery)
We describe the management of a tracheoesophageal fistula due to a damaged tracheal stent, which was first inserted to treat tracheal stenosis. A 29-year-old woman with a history of treated epilepsy had a seizure and suffered from smoke inhalation during a fire. Breathing difficulties appeared and gradually worsened; consultation was obtained two years afterward. After undergoing a thorough examination, the patient was diagnosed with tracheal strangulation. A noncovered, metallic stent was inserted. When the patient was 37 years old, she was admitted to our hospital for the treatment of a tracheoesophageal fistula. We diagnosed it as a tracheoesophageal fistula due to the collapse of the damaged tracheal stent toward the esophageal side, and we decided to perform a mediastinal tracheostomy. Granulation may be formed in the circumference of a stent that has been present for a prolonged period, and removal of the stent may become difficult. This case suggests that insertion of a noncovered, metallic stent is contraindicated for a benign disease.